PERBANDINGAN KINERJA PEGAWAI SEBELUM DAN SEMASA PANDEMI COVID-19 (Studi Kasus Pegawai Dinas Perhubungan Kota Yogyakarta) - Asih Endah Subandiyah; Benedikta Gaudensia Sura (Sekolah Tinggi Ilmu Ekonomi SBI, 2022)
Performance Employee can certainly be relied on by internal and external factors, external factors such as the Covid-19 Pandemic certainly affect the resulting performance and cause differences in work results. Therefore, it is necessary to conduct a performance appraisal using clear and measurable indicators which are used as a reference for performance appraisal, so that we can know what needs to be changed and what is necessary from the existing situation so that it can help improve employee performance in the future. The purpose of this study was to see if there were differences in the performance of the Department Transportation of Yogyakarta before and during the pandemic Covid-19 and whether the results of the employee performance at the Department Transportation of Yogyakarta before the pandemic Covid-19 were better according to the pandemic Covid-19. This research method is comparative with a quantitative approach. The sample used was 51 respondents. The data used in this study are primary data obtained from the distribution of questionnaires of 51 copies, to respondents with the sampling was simple random sampling technique. The data analysis technique used is the validity test, reliability test, normality test, homogeneity test and paired difference test (Paired Sample T-test). The results of this study indicate that the performance of the Yogyakarta City Transportation Department employees before and during the Covid-19 pandemic. Other results indicate that employee performance rewards are productivity and work pressure.